Secondhand smoke from electronic cigarette resulting in hypersensitivity pneumonitis. Issue 3 (22nd March 2020) - Galiatsatos, Panagis; Gomez, Erin; Lin, Cheng Ting; Illei, Peter B; Shah, Pali; Neptune, Enid
Abstract : Cases of vaping-induced lung injury have increased in the USA, resulting in a heterogeneous collection of pneumonitis patterns in persons who used electronic cigarettes. Hypersensitivity pneumonitis has been documented in several cases of first-hand electronic cigarette use; however, secondhand smoke health-related consequences have not been fully understood. We present a case of the patient who developed hypersensitivity pneumonitis secondary to exposure to secondhand smoke from electronic cigarette. We summarise the presentation and diagnostic investigation, as well as the management of this case.